Development of Target Basket Tools for Set-Up and Receive Serve Precise Practice in Volleyball Games (Journal of Physical Education and Sports, 2018)
The purpose of this research is to make design and know the effectiveness of target basket tool which is developed. The research methodology used is research and development. The results showed the quality of the product, based on a volleyball expert's evaluation obtained a mean score of 92.8 with the criteria "very good". The effectiveness of the target basket device is obtained from the comparison data of the feed drill and receive serve using the tool and without the tool by 12 athletes with the test based on the time and number of set-up and receive the same serve. The average difference in the number of tosser set-up is 3; the average time difference of tosser is 0.49 minutes; the average difference between receive-receive libero and defender is 4, and the average time difference between libero and defender is 0.58 minutes with the information that using tools faster and more than without tools, so the target basket tool is effective. The conclusion of this research is the product of effective target basket tool used for set-up and receive serve exercise for an athlete and junior volleyball athlete which also help the ball making so that time and energy more efficiently. An important finding underlying the creation of this target basket tool is the development of drill net tools that also the effectiveness of the tool is very useful for training in improving basic techniques in volleyball. Suggested target basket can be socialized and used for all circles of athletes as it proves to be effective as a training tool.